Strategic alliances for SME development - Das, T. K. 1938- (Research in strategic alliances., 2015)
Strategic Alliances for SME Development is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Strategic Alliances for SME Development contains contributions by leading scholars in the field of strategic alliance research. The 12 chapters in this volume deal with the increasingly significant role of strategic alliances in the development of SMEs, covering such diverse topics as management capability and internationalization of alliance portfolios, building alliances, development drivers, founder ties, competitive edge, strategic alignment, technology and innovative firms, and temporary project alliances. The chapters contain empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on the role of strategic alliances for the development of small and medium-sized enterprises.